Evaluation of an all-in-one hybrid model (EUS Magic Box) for stepwise teaching and training in multiple interventional EUS procedures - Dhir, Vinay; Udawat, Priyanka; Shah, Rahul; Alahari, Aruna (Endoscopy International Open, 2022)
Background and study aims While multiple interventional endoscopic ultrasound (EUS)-guided procedures have evolved over the past two decades, there is no model that allows for training in all of these procedures. We aimed to develop and validate an all-in-one hybrid model for stepwise learning in multiple EUS interventions.Methods A hybrid model was created utilizing a pig esophagus and stomach, a silicon-based duodenum and pancreato-biliary system, a pseudocyst, and biopsy targets. This model was designed to provide hands-on training in multiple interventional EUS procedures, such as EUS-guided fine-needle biopsy (EUS-FNB), biliary drainage (BD), pancreatic duct drainage (PD), pseudocyst drainage (PSD), and gastro-enterostomy (GE). Thirty-six trainees underwent training on this model over 6 days, in two batches. Lumen apposing metal stents were used for PSD and GE. Trainees were assessed for objective criteria of technical difficulties. Subjective assessment by trainees was done via a questionnaire.Results All the trainees were able to complete the requisite steps for all the procedures under supervision. On subjective assessment, 30 trainees (83 %) graded the model as good or excellent. A total of 107 technical difficulties were noted (scope position 55, duct puncture 27, guidewire-related problems 25). Time taken to complete the requisite steps of biopsy, PSD, and GE (10.5 minutes; range 3.5 to 22) was significantly less than that for BD and PD (28 minutes; range 17 to 40) (P < 0.001).Conclusions The hybrid model provided training for multiple EUS interventions with good acceptance by trainees. Stepwise mentoring with the possibility of performing multiple procedures in a single model with or without X-ray could prove useful in conference as well as institutional settings.